Supply Chain Pattern in Digital for Higher Education Management According to Education Criteria for Performance Excellence - Artaphon Chansamut (ExcelingTech, 2022)
The research aims to develop supply chain pattern in digital for higher education management according to education criteria for performance excellence and evaluation of supply chain pattern in digital for higher education management according to education criteria for performance excellence. A sample group consisted of ten experts in the field of supply chain. Data analysis was the average mean and standard deviation. The research was found that the supply chain pattern in digital for higher education management according to education criteria for performance excellence consists of six components namely main suppliers, Manufacture, excellence university , Customers, Satisfaction, feedback The results from ten experts agreement supply chain pattern in digital for higher education management according to education criteria for Performance excellence was a high level. It showed that the pattern is appropriate and applicable to real practice.